Formulation Design and Optimization of Bucco-Mucoadhesive Bilayered Tablet of Propranolol Hydrochloride - J. B. SHUKLA; N. S. PATEL; G. C. PATEL (International Journal of Pharma and Bio Sciences, 2010)
The purpose of present investigation was to develop and optimize bucco mucoadhesive bilayered tablets of Propranolol hydrochloride (PrHCL) using the bioadhesive polymers hydroxyl propyl methyl cellulose (HPMC K4M), xanthan gum (XG) and acrypol 934P (AL-P) individually and in combination along with ethyl cellulose (EC) as an impermeable backing layer. The 32 full factorial design was employed by selecting the independent variables as drug: polymer ratio (X1) and influence of various diluents(X2). Ex- vivo mucoadhesive strength (gm), t50- h and t80- h i.e. time required to release 50% of the drug and 80% of the drug respectively, similarity factor (f2) and swelling index (%S.I) were selected as dependent variables. The tablets were prepared and were evaluated for weight variation, content uniformity, thickness, surface pH, swelling index, in-vitro drug release and ex- vivo mucoadhesion strength. The behaviors of formulations were examined during short time stability studies and were found to be stable.